Memenangkan Persaingan Melalui Keunggulan Sumber Daya Manusia, Teknologi dan Manajemen Waktu - Rini Setiawati (Institut Transportasi dan Logistik Trisakti, 2015)
Globalization certainly faced by Indonesian nation demands efficiency and competitiveness in the business world. The global competition requires the availability of qualified human resources and the vision of excellence. Qualified human resources and the vision of excellence is a determinant factor in the competition between nations. Because globalization is driven by two major forces that technology and trade, the competitiveness of it will depend on ( 1 ) our ability to master technology with a strong science base, and ( 2 ) our ability to build an efficient economic institutions. Secondly it is imperatively be the determining factor in the effort to win the global competition. Thus, efforts to control and develop science and technology is a development agenda in the future, which is very important and urgent to get priority. Globalization: It's about Time too!. Time management is very important in both the private life of individuals as well as in the structure of the organization, especially those relating to managers, ranging from administrators to lini managers